2017
DOI: 10.1097/qai.0000000000001378
|View full text |Cite
|
Sign up to set email alerts
|

Improved HIV and TB Knowledge and Competence Among Mid-level Providers in a Cluster-Randomized Trial of One-on-One Mentorship for Task Shifting

Abstract: One-on-one on-site mentorship improves individual knowledge and competence, has a downstream effect on facility performance, and is a simple approach to training MLPs for task shifting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 15 publications
1
48
0
1
Order By: Relevance
“…In post-mentoring feedback, MLP appreciated the mentoring relationship and reported that it improved their con dence in managing HIV and TB cases. This was demonstrated in the results from the cluster-randomized trial, which showed that mentored MLP handled 50% of HIV clinic consultations compared to 27% by their non-mentored peers, with an improvement in HIV and TB indicators at the facility level such as the proportions of patients who had been offered an HIV test (11). An on-site mentorship approach thus had a cascade effect on clinical practice, patient care, and overall facility performance.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In post-mentoring feedback, MLP appreciated the mentoring relationship and reported that it improved their con dence in managing HIV and TB cases. This was demonstrated in the results from the cluster-randomized trial, which showed that mentored MLP handled 50% of HIV clinic consultations compared to 27% by their non-mentored peers, with an improvement in HIV and TB indicators at the facility level such as the proportions of patients who had been offered an HIV test (11). An on-site mentorship approach thus had a cascade effect on clinical practice, patient care, and overall facility performance.…”
Section: Discussionmentioning
confidence: 98%
“…We describe a 12-month observational study on knowledge, competence and clinical practice among MLP that completed a cluster-randomized trial of one-on-one clinical mentoring. The detailed methods for the cluster-randomized trial are described elsewhere (11) but brie y, the intervention comprised of one-on-one, on-site clinical mentoring of MLP on HIV and TB care from a trained, randomly assigned mentor for 8 hours a week, every 6 weeks, over a nine-month period at each of ve intervention sites; no intervention was provided in control sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training and supervision with feedback occurring alone or together have been shown as interventions that improve health worker performance especially in lower resource settings 27–32. Specifically, studies have looked at the benefits of training on how to write referral notes33 and the use of standard templates to improve quality of such notes from different categories of health workers.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies show that task shifting can have this cost-saving effect [ 23 , 24 ]. There is also some evidence that the synergistic interaction between supervision/mentorship and task shifting can produce facility-level performance improvement [ 25 ]. This is the first study to the authors’ knowledge to examine this interaction as it relates to efficiency in the public sector.…”
Section: Discussionmentioning
confidence: 99%